Comparison of Oral Hygiene Status Between Mango Leaf Extract (Mangifera indica L.) and Povidone Iodine Mouthwash in Fixed Orthodontic Appliance Users - Alamsyah, Yenita; Zia, Hanim Khalida; Kornialia; Mailiza, Fitria; Azipua, Muhammad Haikal (Universitas Muhammadiyah Yogyakarta, 2026)
Fixed orthodontic appliances are commonly used in the treatment of malocclusion; however, their complex components make it difficult for users to maintain oral hygiene. Cleaning can be performed mechanically and chemically, including using mouthwash. Natural ingredients, such as mango leaves (Mangifera indica L.), have potential as alternative mouthwash agents. This study aimed to determine the difference in oral hygiene status between mango leaf extract mouthwash and povidone-iodine mouthwash among users of fixed orthodontic appliances. This study used a pre-test and post-test control group design. The population consisted of 51 users of fixed orthodontic appliances, with 34 participants recruited using total sampling. The participants were divided into two groups: 17 who used mango leaf extract mouthwash and 17 who used povidone-iodine. Data were then analyzed using the Mann–Whitney test. The mean oral hygiene status in the mango leaf extract group decreased from 0.71 before rinsing to 0.09 after rinsing, with a mean difference of 0.62. In the povidone iodine group, the mean decreased from 0.72 to 0.07, with a mean difference of 0.65. In conclusion, there was no significant difference in oral hygiene status between mango leaf extract mouthwash and povidone-iodine mouthwash among users of fixed orthodontic appliances.